Current Devices in TMVI and Their Limitations: Focus on Tendyne - Dahle, Gry (Frontiers in Cardiovascular Medicine, 2020)
Mitral valve regurgitation (MR) has a high incidence in the western world, and mortality is high for untreated severe MR. Catheter based repair was introduced with MitraClip in 2003, and some additional devices later came into the market. To expand the transcatheter treatment options for mitral valve disease, the first transcatheter mitral valve implantation (TMVI) was performed by Søndergaard et al in 2012, only ten years after the first transcatheter aortic valve implantation (TAVI), however, the development has been much slower for the TMVI than for TAVI. From 2012, studies were started for several devices to prove feasibility and safety. However, there were big challenges in valve design; delivery systems and anchoring in addition to anatomical issues (avoid LVOT obstruction and paravalvular leak, big size of annulus). The main valves in studies were CardiaQ (later bought by Edwards Lifesciences, Irvine, USA), Tiara (Neovasc Inc., Richmond, Canada) , Twelve (later Intrepid, Medtronic , MN, USA) and Tendyne™ (Abbott, MN, USA). I will focus on the Tendyne™ valve that is the only CE approved transcatheter mitral valve implant. It is available in a large number of sizes and is repositionable and retrievable. The results for the 100 first patients included in the early feasibility study (EFS) at one and two years are promising. Initially feasible for MR, but further investigations show promising results also for implant in mitral annular calcification.